Calidad microbiológica de la carne de res molida que se expende en la ciudad de Babahoyo - Contreras Heleno, Jubixa Noemi (2024)
The objective of this investigation was to determine the microbiological quality of the ground beef consumed in the city of Babahoyo. It was carried out in the soil laboratory of the Agronomy degree of the Faculty of Agricultural Sciences FACIAG, the total samples of ground beef were 10 with 2 repetitions from the different markets, supermarkets and commissaries of the city of Babahoyo- Los. Rivers. A witness is used to verify the sterility of the solution used and the study area. The determination of the microbiological quality of the ground beef was carried out using the technique of using Petrifilm plates, incubating the samples for 24 h ± 2 h at 37 ºC ± 1 ºC. A "check list" application was used in each store to evaluate sanitary management regarding the handling of ground meat. Within this experimental work, it is concluded that of the 10 samples analyzed, 8 tested positive for E. coli (80%), in which the presence of total Coliforms is also evident in all the samples analyzed (100%). The average values of E. coli (cfu/g) in the ground beef samples exceeded the levels allowed by NTE INEN 1346:2015, which indicates a minimum: 10 cfu/g and a maximum: 100 cfu/g. The average values of total coliforms (cfu/g) exceeded the levels allowed by NTE INEN:2015, which indicates a minimum: 1000000 cfu/g and a maximum: 10000000 cfu/g. The evaluation of the ground meat with the NTE INEN 1346 quality standard determines that the samples analyzed in the markets, butcher shops and supermarkets did not meet the quality parameters, having a concentration greater than the permitted limit of colony-forming units.